Reconciling Progressive Personal Status Regulations with Domestic Public Policy: An Indonesian Paradigm for Cross-Border Adoption Involving Transgender Parents - putri purbasari raharningtyas; Ali Ridho (Universitas Katolik Indonesia Atma Jaya, 2026)
Intercountry child adoption is a highly complex private international law matter involving jurisdictional conflicts, divergent national legal systems, and the protection of child rights. This study examines the current legal framework governing intercountry adoption in Indonesia, compares it with the German legal system and the 1993 Hague Convention, and proposes an implementation timeline and an ideal regulatory model under the Draft Private International Law Act (RUU HPI), along with its realization timeline. The research method employed is a normative juridical couple using statutory, comparative, and conceptual approaches, and analyzing a concrete case of a transgender cross-border couple. The analysis demonstrates that the current sectoral and rigid adoption regulations, which still rely on the Dutch colonial legacy (Algemene Bepalingen van Wetgeving - AB), are no longer adequate to resolve modern cross-border disputes. The comparison with Germany highlights collisions in recognizing the personal status of transgender adoptive parents and the validity of mixed marriages. This study concludes that the enactment of RUU HPI, particularly Articles 13, 35, and 36, offers an ideal regulatory model that adaptively synthesizes the 1993 Hague Convention standards by prioritizing the best interest of the child and the habitual residence principle without compromising domestic public policy.